(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurs face many challenges in today’s ultra-competitive business world. Fortunately, entrepreneurs also have more resources than ever before to tackle those problems.Cash flow is essential to small business survival, yet many entrepreneurs struggle to pay the bills (let alone themselves) while they’re waiting for checks to arrive. Economic development essentially means a process of upward change whereby the real per capita income of the people increases over a period of time. Both Men and Women in business play a vital role in economic development. Entrepreneurs serve as the catalyst in the process of industrialization and economic growth. Technical progress alone cannot lead to economic development, unless technological break through are put to economic use by women and men in business. The study gives a clear idea of constraints and satisfaction of entrepreneurs in coastal area of kanniyakumari district. Majority of the respondents in the age group of 21-30 years young entrepreneurs in the study area. So family members and government have to motivate them to start business. Majority of the respondents are having constraints “lack of idea about import and export”, raising funds and choosing the products. So concerned authorities should take necessary steps to eliminate their problems. Most of the sample respondents are satisfied because they have gained “wider knowledge, self-confidence and leadership qualities”: from their business